La educación ambiental en el proceso de enseñanza aprendizaje de los estudiantes de la Unidad Educativa Pueblo Nuevo, cantón Babahoyo, Provincia Los Ríos - Martinez Lada, Gigi Alexandra (2020)
The objective of this degree work is to implement a Guide to good environmental practices to create environmental responsibility in students, teachers, managers and the community in general of the Pueblo Nuevo Educational Unit through a process of studying environmental education with national policies and international that corresponds to the context of the institution. The solution is important since the human being daily contributes to the degradation of the ecosystem through disastrous and irreversible actions; caused by toxic gases, waste, among others. In the introduction of the document, an analysis of each of the chapters of this titling work was carried out, in order to investigate the problem, the causes and consequences that determine the environmental deterioration, both general and specific objectives in order to raise awareness in the actors involved. In the methodology, a type of bibliographic research is proposed, where a broad search for information on the different topics established in the project raises systematically, based on existing theories, hypotheses, experiments and results on the problems causing environmental deterioration.